2011
DOI: 10.1021/cg200942u
|View full text |Cite
|
Sign up to set email alerts
|

Cyanometallates as Halogen Bond Acceptors

Abstract: Two families of halopyridnium hexacyanometallate salts, (3-XpyMe) 3 [M(CN) 6 ] and (3,5-X 2 pyMe) 3 [M(CN) 6 ] (X = I, Br; 3-XpyMe = N-methyl-3-halopyridinium; 3,5-XpyMe = N-methyl-3,5-dihalopyridinium; M = Cr, Fe, Co), have been synthesized and characterized by single crystal X-ray diffraction. Five of the six members of each family are characterized as isostructural compounds, two structures are reported as solvates, (3-IpyMe) 3 [Fe(CN) 6 ]•2MeCN (2•2MeCN) and (3,5-Br 2 pyMe) 3 [Cr(CN) 6 ]•4H 2 O (10•4H 2 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 99 publications
2
57
0
Order By: Relevance
“…This work was also recently extended to cyanometallates (CÀXÁ Á ÁNCÀM) as halogen bond donors, in a series of halopyridinium salts of hexacyanometallates [M(CN) 6 ] 3À (M¼Cr, Fe, Co) [68]. The geometry of interaction of the halogen bond donor (CÀX) with the cyanide ligand is either a shorter interaction, predominantly with the exo lone pair of the nitrogen atom (CNÁ Á ÁX > 145 ), or a longer interaction with the CN π-bond (CNÁ Á ÁX < 105 ).…”
Section: Metal Complexes With Essentially Metallic Spin Densitymentioning
confidence: 99%
“…This work was also recently extended to cyanometallates (CÀXÁ Á ÁNCÀM) as halogen bond donors, in a series of halopyridinium salts of hexacyanometallates [M(CN) 6 ] 3À (M¼Cr, Fe, Co) [68]. The geometry of interaction of the halogen bond donor (CÀX) with the cyanide ligand is either a shorter interaction, predominantly with the exo lone pair of the nitrogen atom (CNÁ Á ÁX > 145 ), or a longer interaction with the CN π-bond (CNÁ Á ÁX < 105 ).…”
Section: Metal Complexes With Essentially Metallic Spin Densitymentioning
confidence: 99%
“…Ormond-Prout, Smart, and Brammer proposed that halogen bonds can be used to predict and control the process of self-assembly and to fine-tune the electronic properties of cyanometallates. [50] To confirm this assumption they synthesized two types of halopyridium hexacyanometallate salts, (3-XpyMe)3[M(CN)6] and (3, 5-X2pyMe)3[M(CN)6] (X=Cr, Fe, Co). [50] The authors harvested a total of ten crystals, and found out that five out of each family of compounds were isostructural, while other structures were the solvates, (3-IpyMe)3[Fe(CN)6]·2MeCN(2·2MeCN) and (3,5-Br2pyMe)3[Cr(Cr(CN)6]·(10·4H2O).…”
Section: M-x/n/ncs/cn…x Systemsmentioning
confidence: 99%
“…[50] To confirm this assumption they synthesized two types of halopyridium hexacyanometallate salts, (3-XpyMe)3[M(CN)6] and (3, 5-X2pyMe)3[M(CN)6] (X=Cr, Fe, Co). [50] The authors harvested a total of ten crystals, and found out that five out of each family of compounds were isostructural, while other structures were the solvates, (3-IpyMe)3[Fe(CN)6]·2MeCN(2·2MeCN) and (3,5-Br2pyMe)3[Cr(Cr(CN)6]·(10·4H2O). The halogen bonding distances in these structures were shorter than the sum of the van der Waals radii.…”
Section: M-x/n/ncs/cn…x Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown that many properties of the halogen bond are analogous to those of the hydrogen bond [12][13][14]. For example, concerning strength, halogen bonds are comparable to hydrogen bonds and thus a competition may occur between them, thus in recent years much attention has been paid to it [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%